Skrining Fitokimia Polifenol Ekstrak Etanol Daun Ubi Jalar Kuning (Ipomea batatas) dari Madiun - Terza Aflika Happy; Vivin Indrianita; Etik Ainun Rohmah (2023)
Yellow sweet potato (Ipomoea batatas L.) leaves are an easy source of polyphenols because they are often not used after harvest. This leaf began to be used as an herbal ingredient or alternative treatment for the community, empirically showing improvement in conditions and symptoms in Dengue Fever patients. This study determined the content of secondary metabolites from yellow sweet potato leaves. Methods: Research using laboratory testing methods was carried out at the Herbal Materia Medika Laboratory in Batu. Yellow-green sweet potato leaves, as much as 200 grams were collected from the Madiun, East Java. It was extracted by maceration using 2L of ethanol 96% for 2 days and evaporated in a vacuum rotary evaporator to thick extract. Furthermore, phytochemical screening tests were carried out. Results: The results of this study indicated that the yellow sweet potato leaves contained of Alkaloids, Flavonoids, Tannins, Saponins, Terpenoids, Triterpenoids, and Phenols. So the yellow sweet potato leaves are very representative as herbal products.